Mastering Blender - Mullen, Tony, 1971- (Serious skills., 2009)
"Blender, the free alternative for professional-quality 3D animation is a complex program to learn, but once users become familiar with its power, they begin to seek more from it. This book is the first of its kind to explore the more advanced features of Blender so that you can get the most out of the software. You'll take your Blender skills to a whole new level with the featured in-depth coverage of intricate uses for Blender's modeling, texturing, animation, and visual effects tools in a professional environment"--Resource description page.